Redescription of two gekkonid lizard species of the Cyrtodactylus consobrinus (Peters, 1871) complex with comments on online supplementary material. - Hayden R., Davis; Izneil, Nashriq; Kyra S., Woytek; Shanelle A., Wikramanayake; Aaron M., Bauer; Benjamin R., Karin; Ian G., Brennan; Djoko T., Iskandar; Indraneil, Das (Magnolia Press, 2023)
In a recent paper in Zoologica Scripta, the formal diagnoses and descriptions of two new Bornean gekkonid gecko species of the Cyrtodactylus consobrinus (Peters, 1871) complex were included in online supplementary material. Although the new nomina were associated with ZooBank registration identifiers, the supplementary document in which these LSIDs appeared was not published in a format with fixed content and layout. As such, the new nomina cannot be considered to have been promulgated in the electronic version of the paper, as it was not compliant with the International Code of Zoological Nomenclature as amended in 2012. A subsequently published printed version of the paper did make these nomina nomenclaturally available but, following author guidelines, relegated the descriptions and diagnoses, including data critical to justifying recognition of these new cryptic taxa, to online supplementary material. Because of the impermanence of this supplementary document, we here provide the diagnoses, descriptions and type specimen data for these two Cyrtodactylus. We recommend that taxonomists refrain from publishing works containing taxon descriptions and other nomenclatural acts in journals that require critical data to be placed in online supplementary documents.